Distributivity facilitates ACD resolution - Wehbe, Jad; Kinnaird, Kate; Hackl, Martin (Proceedings of the Amsterdam Colloquium, 2024)
Theories of plural predication disagree on the division of labor between the lexical semantics of predicates and various syntactic operators, e.g. the distributivity operator (Krifka 1992; Kratzer 2007). A central issue is whether the LFs giving rise to certain distributive and cumulative readings involve syntactic movement (Beck and Sauerland 2000; Winter 2000). In this project, we adopt the logic of Hackl, Koster-Hale, and Varvoutis (2012) to diagnose movement indirectly via a facilitation effect on ACD resolution. We show that, similar to every, definite plurals under a particular distributive construal decrease the cost of ACD resolution compared to a definite singular baseline. This provides evidence that the distributive reading requires LF-movement of the plural DP hosting ACD above the matrix antecedent of the ellided constituent. We argue that this follows naturally only from theories of distributivity/cumulativity on which there is a syntactically represented distributivity operator that the plural DP needs to outscope in order to get the desired reading.